Leaf anatomical study and ethnobotanical review of selected medicinal species in acanthaceae family and its taxonomic significance - Che Amri, Che Nurul Aini; Shahari, Rozilawati; Mohd Yunus, Noor Syaheera; Midin, Mohd Razik; T., Noraini; A.R., Ruzi; A., Latiff (2023)
The growing interest in the potential medicinal sources from the Acanthaceae is considered as a good starting point for pharmacological research. Leaf anatomy plays a significant role in plant taxonomy as it provides important characteristics that can help in the identification and understanding of relationships among plant species especially for species that have medicinal value. The anatomical study is also significant to avoid misidentification of medicinal species that might lead to incorrect harvesting of raw materials and drug authentication, especially to produce medicines. Therefore, a comprehensive study of leaf anatomy for two species which are Sanchezia speciosa Leonard and Strobilanthes crispa T. Anderson were conducted to assess the leaf anatomical variations that would be useful to identify the plant species. Two species studied were chosen regarding their medicinal value that have been used as traditional remedies to cure diseases such as Sanchezia speciosa that used to treat gastritis in Vietnam. Meanwhile, Strobilanthes crispa or locally known as pecah beling are known to treat kidney stones. Methods used in this study involved several methods such as cross- section using sliding microtome, leaf epidermal peeling, leaf clearing and observation under a light microscope. The common characteristics of leaf anatomy were recorded in the mucilage cells and stomata. Some of the variation features were reported including the trichomes, types of cystolith cells and patterns of anticlinal walls. In conclusion, findings revealed that the leaf anatomical characteristics can be used as additional data to identify incomplete medicinal plant species.